Balanço eletrolítico da ração de suínos em fase inicial submetidos à condição de conforto e estresse térmico - Oliveira, Aparecida da Costa (2012)
This work aimed to study the electrolyte balance of diets on the metabolism of nitrogen balance, blood parameters, urinary pH and physiological response of barrows in the initial phase, in condition of stress and thermal comfort.. For the experiment were used 32 barrows in the early stages, with initial mean body mass of 18.5 ± 0.73. Distributed in experimental design of randomized blocks in a 2x4 factorial design with four replicates of 32 experimental units. The treatments consisted of four isonitrogenous diets with CP: 19.24% BE ration with 168 mEq/kg, R2: BE ration with 212 mEq/kg; R3: BE diet with 256 mEq/kg; R4: ration with EB 300 mEq/kg and two thermal conditions (comfort and stress). The parameters studied were nitrogen ingested, excreted in feces, urine excreted, absorbed, retained, retained/ingested, retained/absorbed, total excretion, protein intake (PBC), excreted in the feces (PBF) and urine (PBU) crude protein retained (PBR), net protein utilization (ULP), glucose, chloride, urea, creatinine, sodium (Na) and potassium (K) in blood plasma, urine pH, environmental conditions of the room, respiratory rate and temperature rectal cancer. The use of feed containing levels of EB between 168 and 300 mEq/kg did not influenced nitrogen balance, protein metabolism and blood parameters of pigs. Pigs exposed to 21 °C have higher consumption, fecal excretion of nitrogen, protein, sodium and potassium plasma than pigs reared under average temperature of 30 °C. Nitrogen retained: intake (%), net protein utilization (%), had higher creatinine values in the condition of thermal stress. The rations containing levels of EB between 168 and 300 mEq/kg to promote linear increase urine pH. The hours of daily observations promoted a positive linear effect (p <0.05) on the physiological parameter (rectal temperature and respiratory rate). The rise in rectal temperature was directly proportional to temperature. The respiratory rate showed an increase (57% above normal) in the heat stress condition